2015
DOI: 10.1177/1078390315580096
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Teaching Method on Performance of Suicide Assessment in Baccalaureate Nursing Students

Abstract: Suicide assessment is a critical assessment skill set that can be effectively taught to nursing students using standardized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…Similarly, the work of Luebbert and Popkess (2015) demonstrated that directed education enhanced the confidence of student nurses in competently assessing suicidality. In summary, if students viewed the promotion of sexual health and well-being as part of their job, and are given support in exploring their values in a safe and structured learning environment, then this should militate against avoidance of the topic when they qualify.…”
Section: Educationmentioning
confidence: 99%
“…Similarly, the work of Luebbert and Popkess (2015) demonstrated that directed education enhanced the confidence of student nurses in competently assessing suicidality. In summary, if students viewed the promotion of sexual health and well-being as part of their job, and are given support in exploring their values in a safe and structured learning environment, then this should militate against avoidance of the topic when they qualify.…”
Section: Educationmentioning
confidence: 99%
“…The methodology across the studies varied significantly in regard to instrument reliability and validity, representative samples and sample size, and the extent to which the study could be classified as program evaluation or research. Luebbert and Popkess (2015) reported that the end of program nursing knowledge was not statistically different for students exposed to simulation than for those taught by traditional methods in the one, only national longitudinal, multisite study that has been conducted on simulation. Shin et al (2015) reported increased levels of confidence and competence with active learning strategies.…”
Section: Discussionmentioning
confidence: 96%
“…The average number of attendees per class in 2010 was the highest, at 5.5; however, each year had approximately 4-5 attendees per class, showing no marked difference among years (Table 3). 4. Although the actual number of members attending classes in 2011 was the highest, at 13, it then decreased to 9 in 2014, which was the same number as in 2010 when the participation of Patient Community members in Community Studies classes was initiated (Table 4).…”
mentioning
confidence: 92%